2013
DOI: 10.1039/c3dt52598h
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst design for iron-promoted reductions: an iron disilyl-dicarbonyl complex bearing weakly coordinating η2-(H–Si) moieties

Abstract: Iron disilyl dicarbonyl complex 1, in which two H-Si moieties of the 1,2-bis(dimethylsilyl)benzene ligand were coordinated to the iron center in an η(2)-(H-Si) fashion, was synthesized by the reaction of (η(4)-C6H8)Fe(CO)3 with 2 equiv. of 1,2-bis(dimethylsilyl)benzene under photo-irradiation. Complex 1 demonstrated high catalytic activity toward the hydrogenation of alkenes, the hydrosilylation of alkenes and the reduction of carbonyl compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 37 publications
2
48
0
1
Order By: Relevance
“…Among the dichloro/iron compounds tested ( Figure 6), one catalyst (namely 1b) hydrosilylated 2-phenyl-but-1-ene with Ph2SiH2 in excellent yields of 92% and 94% enantiomeric excess An iron-disilyl-dicarbonyl complex carrying a 1,2-bis(dimethylsilyl)benzyl ligand that (weakly) coordinated to the iron center in η 2 -(H-Si) was reported by Nagashima and coworkers [15]. This complex successfully catalyzed the hydrosilylation of alkenes (as well as the catalytic hydrogenation of alkenes and the hydrosilane-mediated reduction of carbonyl compounds).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the dichloro/iron compounds tested ( Figure 6), one catalyst (namely 1b) hydrosilylated 2-phenyl-but-1-ene with Ph2SiH2 in excellent yields of 92% and 94% enantiomeric excess An iron-disilyl-dicarbonyl complex carrying a 1,2-bis(dimethylsilyl)benzyl ligand that (weakly) coordinated to the iron center in η 2 -(H-Si) was reported by Nagashima and coworkers [15]. This complex successfully catalyzed the hydrosilylation of alkenes (as well as the catalytic hydrogenation of alkenes and the hydrosilane-mediated reduction of carbonyl compounds).…”
Section: Introductionmentioning
confidence: 99%
“…1968 1972 1976 1980 1984 1988 1992 1996 Due to the increasing demand for silanes and siloxanes by industrial manufacturers, novel hydrosilylation methods [6,7] have been in the focus of research over the last years, particularly since research for alternative platinum-free catalysts containing low-cost-transition metals and/or metalorganic compounds [4,5] is performed extensively. 1968 1972 1976 1980 1984 1988 1992 1996 Due to the increasing demand for silanes and siloxanes by industrial manufacturers, novel hydrosilylation methods [6,7] have been in the focus of research over the last years, particularly since An iron-disilyl-dicarbonyl complex carrying a 1,2-bis(dimethylsilyl)benzyl ligand that (weakly) coordinated to the iron center in η 2 -(H-Si) was reported by Nagashima and coworkers [15]. This complex successfully catalyzed the hydrosilylation of alkenes (as well as the catalytic hydrogenation of alkenes and the hydrosilane-mediated reduction of carbonyl compounds).…”
Section: Introductionmentioning
confidence: 99%
“…The group of Nagashima reported in 2013 an iron disilyl complex with an η 2 -(H-Si) coordinating 1,2-bis(dimethylsilyl)benzene (BDSB) ligand, which exhibited a high catalytic activity for the 561 hydrogenation of alkenes and hydrosilylation of alkenes, amides, aldehydes, ketones and esters. 67 For the reduction of aldehydes and ketones, 1 mol% of the iron complex ( Figure 16 Aiming to orient the reader into the advances made on the iron-catalyzed hydrosilylation of 576 carbonyls in terms of applicability in laboratory settings, Table 1 summarize the iron-based catalysts revised on this work, gathering the experimental conditions for the utilization of the most relevant catalytic systems that appear in the literature. The included data correspond to the optimized or most representative conditions employed for the reduction of acetophenone or either benchmark ketone tested in each case.…”
Section: Phosphorus-based Ligandsmentioning
confidence: 99%
“…63 Tolman, Ittel and co-workers reported that a Cyclometalation reactions are known to transform carbon-hydrogen bonds into carbon-metal bonds that usually form five-membered metallacyclic ring species. 65 In ruthenium and rhodium catalysis, the carbon-carbon bond-forming reactions proceed preferentially by using an anchoring group, which contains nitrogen, phosphorus, 3d,22f,23,68,69 In general, the use of diarylzinc reagent, that generated in situ from an equivalent of ZnCl 2 •TMEDA (where TMEDA = N,N,N',N'-tetramethylethylenediamine) 74 The reaction of 2-phenylpyridine with an excess of 2-norbornene proceeded smoothly at 80 ºC for 12 h by using a stoichiometric amount of the well-defined iron complex 25 to afford the desired ortho C-H alkylated product in high yield (Scheme 1.22). 72 Apart from the stoichiometric C-H bond functionalization of arenes, iron complex 25 could also demonstrate high catalytic activity towards hydrogenation and hydrosilylation of alkenes at room temperature.…”
Section: Aromatic C-h Bond Activation By Iron Complexesmentioning
confidence: 99%
“…72 Apart from the stoichiometric C-H bond functionalization of arenes, iron complex 25 could also demonstrate high catalytic activity towards hydrogenation and hydrosilylation of alkenes at room temperature. 74 Scheme 1.22. Stoichiometric Iron-Mediated C-H Bond Alkylation of 2-Phenylpyridine…”
Section: Aromatic C-h Bond Activation By Iron Complexesmentioning
confidence: 99%